Tailored electric and optical properties of Nd doped ZnO: from transparent conducting oxide to photon down-shifting thin films. Issue 47 (26th April 2016) - Nistor, M.; Mihut, L.; Millon, E.; Cachoncinlle, C.; Hebert, C.; Perrière, J.
Abstract : Tunable properties from transparent conducting to photon down-shifting are obtained with slight change in O2 pressure during Nd:ZnO film growth. Abstract : Nd-doped ZnO films with highly tunable properties were grown by pulsed electron beam deposition at 500 °C on Si and c-cut single crystal substrates under oxygen gas. The effects of a slight change in the oxygen pressure (10 −2 to 2 × 10 −2 mbar) on the composition, structure and physical properties of the films were studied. Films grown at 10 −2 mbar present a low resistivity (5 × 10 −3 Ω cm) and high transparency in visible range and do not show any near-infrared emission due to Nd 3+ ions. On the contrary, films grown at 2 × 10 −2 mbar have high resistivity (>16 Ω cm), high optical transparency and near infrared emission of the Nd 3+ ions is observed under indirect excitation at 335 nm ( i.e. absorption by the ZnO matrix and transfer to Nd 3+ ions). These significant changes in physical properties, leading from transparent conducting oxide to photon down-shifting thin films, are related to growth mode in pulsed-electron beam deposition.